Safety of limb-salvaging surgery for sarcomas compromising major vessels: A 15-year single-centre outcomes study. Issue 9 (September 2021) - Berner, Juan Enrique; Dearden, Alexander; Magdum, Ashish A.; Crowley, Timothy P.; Rankin, Kenneth; Clarke, Michael J.; Ragbir, Maniram
Summary: Introduction: Limb-threatening sarcomas invading major vessels present an oncological and reconstructive challenge. Curative resection involves either performing an amputation or an immediate reconstruction of the invaded vessels. We present our 15-year experience of these cases at the North of England Bone and Soft Tissue Tumour Service. Materials and methods: A Strengthening the Reporting of Observational studies in Epidemiology (STROBE) compliant retrospective review of our prospective database was performed including patients who required major vessel reconstruction following sarcoma excision from 2003 until 2018. Patient demographic data along with tumour and histological subtypes, treatment modality, complications and outcomes were inquired. Autologous and prosthetic vessel reconstruction approaches were compared. Results: Nineteen patients were identified with the most common tumour locations being the thigh and groin areas. Five cases involved recurrent tumours. Clear resection margins were obtained in 15 cases. Autologous vein grafts were preferred over polytetrafluoroethylene (PTFE) prosthesis in 17 cases. A pedicled flap or free flap was required to achieve adequate soft tissue cover in six patients, while the rest underwent primary closure. Five patients lost the patency of the reconstructed vessels with one of these requiring an amputation. The estimated disease-specific survival at 5 years was 58%. Discussion: Limb-preservation surgery in the context of vessel compromise is not only safe, but also a functionally and psychosocially beneficial means of avoiding an amputation. We believe that careful pre-operative planning and discussion in a multidisciplinary setting is key for obtaining positive outcomes.